2015
DOI: 10.1111/bph.13184
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate induces necroptosis in colon cancer cells through GSH depletion/ROS increase/MAPKs activation pathway

Abstract: BACKGROUND AND PURPOSEDimethyl fumarate (DMF) is a newly approved drug for the treatment of relapsing forms of multiple sclerosis and relapsing-remitting multiple sclerosis. Here, we investigated the effects of DMF and its metabolites mono-methylfumarate (MMF and methanol) on different gastrointestinal cancer cell lines and the underlying molecular mechanisms involved. EXPERIMENTAL APPROACHCell viability was measured by the MTT or CCK8 assay. Protein expressions were measured by Western blot analysis. LDH rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 56 publications
(74 reference statements)
3
91
1
Order By: Relevance
“…PM induced acute and chronic effects via an inflammatory mechanism of oxidative stress [30-32], and PM could play an important role in adverse respiratory effects through generating ROS in the respiratory tract [33]. Substantial evidence accumulated to show that reactive oxygen species (ROS) have long been considered to be a driving force for necroptosis [34-36]. A recent study showed that mitoROS promoted RIP1 autophosphorylation via modification of three crucial cysteine residues, and this phosphorylation event allowed efficient recruitment of RIP3 to RIP1 to form a functional necrosome for TNF-induced necroptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…PM induced acute and chronic effects via an inflammatory mechanism of oxidative stress [30-32], and PM could play an important role in adverse respiratory effects through generating ROS in the respiratory tract [33]. Substantial evidence accumulated to show that reactive oxygen species (ROS) have long been considered to be a driving force for necroptosis [34-36]. A recent study showed that mitoROS promoted RIP1 autophosphorylation via modification of three crucial cysteine residues, and this phosphorylation event allowed efficient recruitment of RIP3 to RIP1 to form a functional necrosome for TNF-induced necroptosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…As ROS was also actively involved in necroptosis induced by stimulus such as TNF [34], and small molecules dimethyl fumarate [35], [36] etc, its roles in t-BHP induced necroptosis were further explored. T-BHP H induced ROS formation was inhibited by mitochondrial respiratory chain inhibitors but not by NADPH oxidase inhibitor suggesting that mitochondria could be the main source of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a protective role when cells encounter environmental stresses, such as starvation or pathogen infection [34, 35]. This type of autophagy benefits cell survival, but excessive autophagy can result in autophagic cell death [36]. Accordingly, induction of excessive autophagy has been regarded as a new therapeutic strategy [37].…”
Section: Discussionmentioning
confidence: 99%